An Analysis of the Relevance of Humanistic Learning Theory within the Context of Islamic Education - Saprin S; Mustari M; M Firdaus; Surdi Pabbe (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the relevance of humanist learning theory to Islamic education. Humanist learning theory focuses on optimally developing human potential through freedom of learning and meaningful experiences. Meanwhile, Islamic education emphasizes the formation of the whole person (insan kamil) based on the values of monotheism, morality, and human nature. This study used a qualitative method with a library research approach sourced from educational psychology books and scientific works in the field of Islamic education. The results show that humanist learning theory aligns with the principles of Islamic education in terms of respect for student potential, the role of teachers as guides, and student-centered learning. However, there are fundamental differences in philosophical aspects: humanist theory is oriented towards humans (anthropocentric), while Islamic education is centered on divine values (theocentric). Thus, the application of humanist theory in Islamic education needs to be directed at strengthening spiritual values so that the educational process does not lose its divine dimension.